Anti-electromagnetic interference high-frequency lightweight nano new material

Through composite materials of graphene quantum dots, multi-wall carbon nanotubes, ferrite nanoparticles and polymer matrix, the shortcomings of existing electromagnetic shielding materials in high-frequency electromagnetic wave shielding performance, lightweight, mechanical properties and high temperature stability are solved, and efficient electromagnetic wave shielding and excellent mechanical properties are achieved.

CN119798956AInactive Publication Date: 2025-04-11PINGDINGSHAN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510079817.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have shortcomings in high-frequency electromagnetic wave shielding efficiency, lightness, mechanical properties and high temperature stability, and are difficult to meet the strict requirements in the fields of modern electronic equipment, communication equipment and aerospace.

Method used

A composite material composed of graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and polymer matrix (such as polyether etherketone or polyimide) is used to ensure the uniform distribution and good combination of each component through processes such as sonication, solvent impregnation and hot pressing molding, and improve the electromagnetic wave shielding and mechanical properties of the material.

Benefits of technology

It realizes effective shielding of high-frequency electromagnetic waves, provides electromagnetic wave shielding performance of more than 50dB, improves the lightness, mechanical strength and high temperature stability of the material, and is suitable for applications in multiple high-frequency electromagnetic interference environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005248232990000191
    Figure BDA0005248232990000191
  • Figure BDA0005248232990000192
    Figure BDA0005248232990000192
  • Figure BDA0005248232990000201
    Figure BDA0005248232990000201
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic shielding materials, and discloses an anti-electromagnetic interference high-frequency lightweight nano new material, which is composed of 10-35% of graphene quantum dots, 5-20% of multi-walled carbon nanotubes, 5-20% of ferrite nanoparticles and 10-30% of a polymer matrix. The content of the ferrite nanoparticles is 15%-25%, and the content of the polymer matrix is 40%-55%; according to the composite material, through the synergistic effect of the graphene quantum dots, the multi-walled carbon nanotubes and the ferrite nanoparticles, the electromagnetic shielding effectiveness, the mechanical strength, the thermal stability and the lightweight property of the composite material are remarkably improved, and the composite material is particularly suitable for the fields of high-frequency electronic equipment, communication equipment and aerospace; the material has good processability, stable performance and efficient electromagnetic interference shielding capability, and can meet the requirements of modern high-frequency equipment on light, high-temperature-resistant and efficient shielding materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic shielding materials, in particular to a new high-frequency lightweight nano material that is resistant to electromagnetic interference. Background Art

[0002] With the continuous development of science and technology, the frequency of modern electronic equipment and communication systems has gradually extended to high frequency bands (such as microwaves, millimeter waves, etc.). At the same time, the problem of electromagnetic interference (EMI) is becoming more and more serious, especially in high-frequency equipment, where electromagnetic interference can significantly affect the performance and reliability of the equipment. In order to meet this challenge, electromagnetic shielding materials have been widely used in electronics, communications, aerospace and other fields. The main function of electromagnetic shielding materials is to effectively absorb, reflect or attenuate electromagnetic waves to prevent external electromagnetic waves from interfering with sensitive equipment, while also preventing the leakage of electromagnetic waves from the equipment itself, protecting the environment and people from unnecessary electromagnetic radiation.

[0003] Existing electromagnetic shielding materials mainly rely on metal materials, conductive polymers, carbon-based materials, and ferrites. However, these materials often have the following problems: First, although metal materials have excellent electromagnetic shielding performance, due to their high density, they are not suitable for scenes that require light weight and high strength; second, although conductive polymers have improved in light weight, their electromagnetic shielding performance is relatively low, and their antioxidant performance is poor and they are prone to aging; carbon-based materials such as graphene and carbon nanotubes have good electromagnetic wave absorption capabilities, but their shielding performance in high-frequency bands is often limited by the conductivity and dispersibility of the materials, and their poor binding with the polymer matrix limits their scope of application.

[0004] In addition, existing ferrite materials have certain advantages in electromagnetic wave shielding, especially in the magnetic loss effect in the high frequency band, but due to their high density and relatively poor mechanical properties, they are usually unable to meet the requirements of light weight and high strength in applications. Therefore, how to ensure the effectiveness of electromagnetic wave shielding while improving the material's lightness, mechanical strength and stability at high frequencies has become an urgent problem to be solved. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a new high-frequency lightweight nano material that is resistant to electromagnetic interference, which solves the deficiencies of the existing electromagnetic shielding materials in terms of high-frequency electromagnetic wave shielding effectiveness, lightness, mechanical properties and high-temperature stability.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] On the one hand, the present invention provides a new high-frequency lightweight nano material that is resistant to electromagnetic interference. The material includes graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and a polymer matrix. The content of the graphene quantum dots is 10% to 35%, the content of the multi-walled carbon nanotubes is 5% to 20%, the content of the ferrite nanoparticles is 15% to 25%, and the content of the polymer matrix is ​​40% to 55%.

[0008] Preferably, the particle size of the graphene quantum dots is 1 to 10 nm, and the surface functional groups of the graphene quantum dots are carboxyl, hydroxyl or amino groups.

[0009] Preferably, the surface of the multi-walled carbon nanotube has oxide groups, and amino groups or carboxyl groups are introduced through chemical modification.

[0010] Preferably, the particle size of the ferrite nanoparticles is 5 to 20 nm, and the surface of the ferrite nanoparticles has amino or fluorine functional groups.

[0011] Preferably, the polymer matrix is ​​polyetheretherketone or polyimide, and the molecular weight of the polymer matrix is ​​100,000 to 300,000.

[0012] Another aspect of the present invention provides a method for preparing a high-frequency lightweight new nano material that is resistant to electromagnetic interference, comprising the following steps:

[0013] (1) mixing graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and a polymer matrix to form a uniform dispersion;

[0014] (2) uniformly distributing graphene quantum dots, multi-walled carbon nanotubes, and ferrite nanoparticles in a polymer matrix by ultrasonic treatment and solvent impregnation;

[0015] (3) forming the composite material into a desired shape by a hot pressing method;

[0016] (4) Perform high temperature annealing treatment to optimize the microstructure of the composite material.

[0017] Preferably, the ultrasonic frequency of the ultrasonic treatment step is 20kHz to 40kHz, the ultrasonic time is 30 minutes to 60 minutes, and the ultrasonic power is 100W to 300W.

[0018] Preferably, the immersion time of the solvent immersion method is 10 to 15 minutes, the immersion temperature is 30° C. to 40° C., and the solvent is dimethylformamide or N,N-dimethylacetamide.

[0019] Preferably, the hot pressing molding temperature is 150° C. to 200° C., the hot pressing pressure is 5 to 10 MPa, and the hot pressing time is 10 to 20 minutes.

[0020] Preferably, the annealing temperature of the high temperature annealing treatment is 200° C. to 300° C., and the annealing time is 2 to 4 hours.

[0021] The present invention provides a new high-frequency lightweight nano material that is resistant to electromagnetic interference and has the following beneficial effects:

[0022] 1. The composite material of the present invention significantly improves the shielding effectiveness of high-frequency electromagnetic waves through the synergistic effect of graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles. The composite material can not only effectively absorb and attenuate electromagnetic waves, but also provide electromagnetic wave shielding effectiveness of more than 50dB in the high-frequency band, meeting the strict requirements of modern electronic equipment, communication equipment and aerospace fields for electromagnetic interference shielding.

[0023] 2. The present invention uses polyetheretherketone and polyimide as the matrix material, combined with the composite effect of graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles, so that the composite material shows significant improvement in tensile strength and flexural strength. In particular, the polymer structure of the polymer matrix enhances the mechanical strength of the composite material, ensuring the stability of the material under high load and harsh environment.

[0024] 3. The composite material of the present invention maintains a relatively low density, especially when a lightweight matrix material such as polyetheretherketone and polyimide is used, thereby ensuring the weight advantage of the material.

[0025] 4. The present invention improves the dispersibility of graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles through surface functionalization technology. Through chemical modification, the uniform distribution of nanomaterials in the polymer matrix is ​​ensured, and the overall performance of the composite material is improved. Good interface bonding not only enhances the mechanical strength of the composite material, but also optimizes the electromagnetic wave absorption effect, ensuring the stability of the material and efficient electromagnetic shielding capability.

[0026] 5. The composite material of the present invention has good processability and can be mass-produced through conventional hot pressing and high-temperature annealing. The material can maintain stable performance under the requirements of complex shapes and sizes, and is suitable for multiple fields, including but not limited to high-frequency electronic equipment, communication systems, aerospace devices, etc., to meet the needs of different application scenarios.

[0027] 6. The graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles used in the present invention are all sustainable and environmentally friendly nanomaterials, and the polymer matrix material used in the composite material has high durability and recyclability. The production and application process of the material has little impact on the environment and meets modern green environmental protection requirements. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] The present invention provides a high-frequency, lightweight, and anti-electromagnetic interference new nanomaterial, which includes graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles, and a polymer matrix. The innovation of the material lies in the specific proportion of its composition and the synergistic effect between the materials, which ensures the material's effective absorption and shielding capabilities of electromagnetic waves in the high-frequency band, while maintaining the characteristics of lightness and high strength, and is suitable for applications in high-frequency electromagnetic interference environments.

[0030] The specific contents of graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and polymer matrix in the present invention are as follows: the content of graphene quantum dots is 10% to 35%, the content of multi-walled carbon nanotubes is 5% to 20%, the content of ferrite nanoparticles is 15% to 25%, and the content of polymer matrix is ​​40% to 55%. The specific proportions of these components are determined based on their optimal combination in electromagnetic wave shielding, material mechanical strength, light weight characteristics and process performance.

[0031] The particle size of graphene quantum dots is between 1 and 10 nm, and they have extremely high specific surface area and excellent electrical conductivity. The role of graphene quantum dots in the present invention is to utilize their good electromagnetic wave absorption characteristics to effectively absorb electromagnetic wave energy within the frequency range of high-frequency electromagnetic waves (especially millimeter waves and microwave bands). The surface functional groups of graphene quantum dots, such as carboxyl, hydroxyl or amino groups, can improve their interfacial compatibility with other components and improve their dispersibility in composite materials, thereby avoiding agglomeration and ensuring effective attenuation of electromagnetic waves.

[0032] Multi-walled carbon nanotubes can form a three-dimensional conductive network in composite materials through their one-dimensional conductive structure and excellent conductive properties. This network effectively promotes the scattering, reflection and absorption of electromagnetic waves, especially in the high-frequency band. Through surface oxidation and the introduction of functional groups such as amino and carboxyl groups, the surface affinity of carbon nanotubes is enhanced, thereby improving their interfacial bonding with graphene quantum dots and ferrite nanoparticles, and enhancing the overall conductivity of the composite material and the scattering ability of electromagnetic waves.

[0033] Ferrite nanoparticles, as magnetic materials, have strong magnetism and good electromagnetic wave absorption ability. Its particle size is 5 to 20nm, and its surface has amino or fluorine functional groups to enhance compatibility with other components. Ferrite nanoparticles effectively absorb electromagnetic waves through magnetic loss mechanisms, especially in microwave and millimeter wave bands, and can significantly reduce the intensity of electromagnetic waves. The addition of ferrite nanoparticles further enhances the electromagnetic wave attenuation ability of the composite material, making the composite material show excellent shielding effect in different frequency bands.

[0034] The role of the polymer matrix such as polyetheretherketone (PEEK) or polyimide (PI) in the present invention is not only to serve as a supporting material to provide stability of the overall structure, but also to optimize the mechanical strength of the composite material through its own excellent electrical properties and thermal stability. The polymer matrix has a lower density, so that the composite material maintains its lightweight characteristics. The selection of the polymer matrix ensures that the composite material can still maintain a stable electromagnetic shielding effect and structural strength under high temperature and harsh environment.

[0035] In summary, the synergistic effect of the components in the material of the present invention is achieved through the following mechanisms: first, the role of graphene quantum dots in electromagnetic wave absorption enhances the absorption of high-frequency electromagnetic waves through its quantum effect; second, multi-walled carbon nanotubes promote the scattering and reflection of electromagnetic waves through their conductive network; ferrite nanoparticles effectively absorb electromagnetic waves through magnetic loss effect and reduce the intensity of electromagnetic waves. The polymer matrix provides the necessary support and mechanical strength for the composite material, while also ensuring the lightweight characteristics of the material. The interaction between different components is enhanced through the optimization of surface modification and interface engineering, so that the composite material exhibits excellent performance in high-frequency electromagnetic interference shielding.

[0036] The material of the present invention can not only effectively shield high-frequency electromagnetic waves, especially in the millimeter wave and microwave frequency bands, but also has the characteristics of lightness, stability and high strength, and is suitable for electromagnetic interference protection in the fields of electronic equipment, communication equipment, radar systems, and aerospace devices.

[0037] The surface functionalization of graphene quantum dots in the present invention is achieved by chemical oxidation and reduction methods to introduce different functional groups, such as carboxyl (-COOH), hydroxyl (-OH) and amino (-NH 2 ) to improve its dispersibility, interfacial bonding and electromagnetic wave absorption performance. Specifically, graphene quantum dots are first generated through an oxidation reaction, and then their surface is functionalized to ensure optimal performance in the composite material.

[0038] In terms of carboxyl (-COOH) functionalization, carboxyl groups are introduced on the surface of graphene quantum dots by reacting graphene quantum dots with concentrated nitric acid and hydrogen peroxide. The specific steps are:

[0039] The graphene quantum dots are dissolved in concentrated sulfuric acid, and an appropriate amount of concentrated nitric acid is added and heated to 50° C. to 70° C., and reacted at this temperature for 4 to 6 hours.

[0040] Through this method, a large number of carboxyl groups are generated on the surface of graphene quantum dots, which in turn enhances their hydrophilicity and surface activity and improves their interfacial compatibility with other components (such as carbon nanotubes and ferrite nanoparticles).

[0041] In terms of hydroxyl (-OH) functionalization, the surface structure of graphene oxide is reduced to produce hydroxyl groups on its surface. A common reduction method is to use a reducing agent such as sodium hydride or ammonia. The specific steps are:

[0042] The graphene quantum dots are dispersed in deionized water, sodium hydride or ammonia water is added, and the reaction is stirred for 2 to 4 hours to complete the reaction at room temperature.

[0043] This method can introduce hydroxyl groups, which significantly improves the dispersibility of graphene quantum dots in aqueous solution and exhibits stronger interfacial bonding in composite materials.

[0044] For amino groups (-NH 2 ) functionalization, by using aminosilane reagents to introduce amino groups into the surface of graphene quantum dots, commonly used aminosilane reagents include 3-aminopropyltriethoxysilane (APTES). The specific steps are:

[0045] The graphene quantum dots were dissolved in deionized water, 3-aminopropyltriethoxysilane (APTES) was added, and the mixture was stirred and reacted at 60° C. to 80° C. for 3 to 6 hours.

[0046] The amino group can improve the bonding force between graphene quantum dots and other materials, and enhance the electrical conductivity and electromagnetic wave absorption performance of the composite material, especially in the high frequency band.

[0047] Through the above surface functionalization treatment, the dispersibility and interface binding force of graphene quantum dots are significantly improved, and their electromagnetic wave absorption effect in composite materials is enhanced. Different functional groups give graphene quantum dots different properties: carboxyl groups enhance hydrophilicity, hydroxyl groups enhance dispersibility, and amino groups enhance interface binding force and electromagnetic wave absorption capacity.

[0048] These surface modifications enable graphene quantum dots to form stronger synergistic effects with multi-walled carbon nanotubes, ferrite nanoparticles and polymer matrices, thereby significantly improving the electromagnetic shielding effect of the composite material.

[0049] In the present invention, the surface functionalization of multi-walled carbon nanotubes is carried out by introducing oxide groups through chemical modification, and further by introducing amino groups (-NH 2) or carboxyl (-COOH) groups to improve its interfacial bonding with other components and enhance the electromagnetic wave absorption performance and mechanical strength of the composite material. The specific functionalization steps are completed through the following process.

[0050] First, in order to introduce oxide groups, the multi-walled carbon nanotubes are surface modified by acidification. Usually, a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is used to generate oxide groups (such as -OH, -COOH) on the surface of the multi-walled carbon nanotubes by the oxidation effect of the strong acid. This treatment process can be achieved by the following steps:

[0051] Dissolve the multi-walled carbon nanotubes in a mixture of concentrated sulfuric acid and concentrated nitric acid, usually with a volume ratio of nitric acid to sulfuric acid of 1:3, and react at a temperature of 50°C to 70°C for 4 to 6 hours to ensure complete reaction.

[0052] In this process, the strong oxidant oxidizes the surface of the carbon nanotubes to generate a surface containing oxide groups such as hydroxyl and carboxyl. After the reaction is completed, the solution is cooled and washed with a large amount of deionized water to remove the residual acidic substances, and then separated by centrifugation to obtain the carbon nanotubes with oxide groups on the surface.

[0053] Next, the amino group (-NH 2 ) or carboxyl (-COOH) groups. This process can be achieved by selecting appropriate chemical reagents. For example, amino groups can be chemically grafted using aminosilane reagents, such as 3-aminopropyltriethoxysilane (APTES).

[0054] In this process, the oxidized carbon nanotubes are first dispersed in deionized water, and then an appropriate amount of aminosilane is added and stirred for 3 to 6 hours at a temperature of 60°C to 80°C. Aminosilane reacts chemically with the oxidized groups on the surface of multi-walled carbon nanotubes through its amino groups, successfully grafting the amino groups to the surface of the carbon nanotubes, enhancing their interfacial bonding with other materials.

[0055] Similarly, the introduction of carboxyl (-COOH) groups can also be achieved through similar chemical grafting reactions. For example, chemical reagents containing carboxyl groups, such as epoxy chloropropane or terephthaloyl chloride, can be used. The specific operation is:

[0056] The oxidized multi-walled carbon nanotubes and carboxyl reagents are dissolved in an appropriate amount of solvent and reacted at 80°C to 100°C for 2 to 4 hours to promote the combination of carboxyl groups with oxide groups on the surface of carbon nanotubes and successfully introduce carboxyl groups. This step can further improve the surface hydrophilicity of carbon nanotubes and compatibility with other materials (such as graphene quantum dots and ferrite nanoparticles).

[0057] Through the above steps, the introduction of oxide groups, amino groups or carboxyl groups significantly improves the dispersibility of multi-walled carbon nanotubes in the composite material, while also improving its binding force with the polymer matrix and other nano components. The introduction of amino groups helps to improve the conductivity and electromagnetic wave absorption performance of carbon nanotubes, especially in the high frequency band. The carboxyl groups enhance the hydrophilicity of carbon nanotubes, making it easier to combine with the aqueous polymer matrix, thereby enhancing the mechanical properties and stability of the composite material.

[0058] In the present invention, the surface functionalization of ferrite nanoparticles is achieved by introducing amino groups (-NH 2 ) or fluorine (-F) groups to improve its compatibility with other components, enhance the electromagnetic wave absorption performance and the mechanical strength of the composite material. Specifically, the surface functionalization of ferrite nanoparticles is achieved by chemical modification methods. The following are the specific technical steps.

[0059] First, the amino group (-NH 2 ) is introduced through aminosilane chemical reaction. Usually, a silane reagent with amino function, such as 3-aminopropyltriethoxysilane (APTES), is selected to react with ferrite nanoparticles to form a stable amino layer. The specific steps are:

[0060] The ferrite nanoparticles are first dispersed in anhydrous ethanol or deionized water, and 3-aminopropyltriethoxysilane (APTES) is added. The reaction is stirred at a temperature of 60°C to 80°C for 3 to 6 hours to ensure that the amino groups are evenly grafted onto the surface of the ferrite nanoparticles. After the reaction is completed, the unreacted reagents are removed by centrifugation and washing steps to obtain ferrite nanoparticles with amino groups on the surface.

[0061] Secondly, the introduction of fluorine groups (-F) can be achieved through fluorination. Usually, ammonium fluoride (NH 4 F) or hydrogen fluoride (HF) as a fluorine source, and introduce fluorine groups into the surface of ferrite nanoparticles through reaction. The specific steps are:

[0062] The ferrite nanoparticles are dissolved in an ammonium fluoride solution, the solvent is deionized water or ethanol, the reaction temperature is set at 50°C to 70°C, and the reaction time is 3 to 6 hours. After the reaction is completed, byproducts such as ammonium fluoride are removed by filtering and washing to obtain ferrite nanoparticles with fluorine-based functional groups on the surface.

[0063] The introduction of fluorine groups not only improves the surface hydrophobicity of ferrite nanoparticles, but also enhances their binding force with other hydrophobic materials and optimizes the overall performance of the composite material.

[0064] Through the above two methods, amino and fluorine functional groups are introduced into the surface of ferrite nanoparticles, thereby improving their compatibility and interfacial bonding with other components. The amino group can improve the hydrophilicity of ferrite nanoparticles, enabling them to better combine with the aqueous polymer matrix and enhance the mechanical strength of the composite material. The fluorine group can increase the hydrophobicity of ferrite nanoparticles, enhance their dispersibility in the hydrophobic matrix, and help improve the effect of the composite material in high-frequency electromagnetic wave absorption.

[0065] These surface functionalized ferrite nanoparticles in the composite material of the present invention work synergistically with other components (such as graphene quantum dots, multi-walled carbon nanotubes and polymer matrix) to effectively enhance the electromagnetic wave absorption capacity of the material. Through amino or fluorine-based functionalization, the ferrite nanoparticles not only show better dispersibility in the composite material, but also enhance the electromagnetic interference shielding ability of the material through the magnetic loss effect.

[0066] In summary, ferrite nanoparticles functionalized with amino and fluorine groups not only improve the dispersibility and interfacial bonding strength of the composite materials, but also significantly improve the electromagnetic shielding effectiveness of the materials, especially in high-frequency applications, showing excellent electromagnetic wave absorption properties.

[0067] In the present invention, the polymer matrix is ​​polyetheretherketone (PEEK) or polyimide (PI), and its molecular weight is 100,000 to 300,000. The role of these polymer matrices in the composite material is not only to provide structural support, but also to optimize the performance of the composite material through its own chemical and physical properties, especially in terms of electromagnetic interference shielding, mechanical strength, thermal stability, etc.

[0068] Both polyetheretherketone (PEEK) and polyimide (PI) have excellent mechanical properties, including high tensile strength, compressive strength and flexural strength. Their molecular weight ranges from 100,000 to 300,000, ensuring good fluidity and formability of the polymer matrix while providing the necessary structural support in the composite material. The high molecular weight of the polymer matrix can enhance the cohesion of the material, giving the composite material strong tensile strength and deformation resistance, thereby ensuring that the material remains stable under high loads.

[0069] Both PEEK and PI have excellent thermal stability and can maintain their performance for a long time in high temperature environments. Polyetheretherketone has a high heat deformation temperature and glass transition temperature (Tg), so that the composite material will not soften or deform at high operating temperatures. Polyimide has excellent high temperature stability and heat resistance, and can maintain good mechanical strength and electromagnetic shielding effectiveness at temperatures above 400°C. This makes the composite material of the present invention suitable for electromagnetic interference shielding needs in extreme high temperature environments, such as aerospace, electronic equipment and other fields.

[0070] The polymer matrix itself has a low dielectric constant and small dielectric loss, but its good dispersion performance and compatibility with conductive nanomaterials enable it to effectively enhance the electromagnetic wave shielding effect of the composite material. The polymer matrix optimizes the propagation path of electromagnetic waves by forming a uniform composite with graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles. The synergistic effect of the polymer matrix and these functional nanomaterials enhances the composite material's ability to reflect, absorb and scatter electromagnetic waves, especially in the high-frequency band, with excellent electromagnetic wave shielding effect.

[0071] PEEK and PI materials have a lower density, which can effectively reduce the overall weight of composite materials. Especially in applications with strict weight requirements such as aerospace and mobile communications, the lightweight characteristics of composite materials ensure efficient electromagnetic shielding while avoiding the heavy burden that traditional shielding materials may bring.

[0072] The polymer matrix has good surface properties, so that graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles can be well dispersed in it. Through the polymer chain structure and surface energy of the polymer matrix, the interfacial bonding force between the components in the composite material can be enhanced, promoting the synergistic effect of electromagnetic wave absorption. The molecular weight of the polymer matrix in the range of 100,000 to 300,000 ensures the fluidity and uniformity of the dispersion, thereby ensuring that the nanomaterials can be evenly distributed in the matrix.

[0073] The role of the polymer matrix in the present invention is mainly reflected in providing structural support for the composite material, enhancing mechanical strength, improving thermal stability and optimizing electromagnetic wave shielding performance. The selection of polyetheretherketone and polyimide, combined with the appropriate molecular weight range, ensures the performance of the composite material in high temperature, high strength and high frequency electromagnetic interference environment. The polymer matrix not only improves the stability and durability of the composite material, but also significantly enhances the electromagnetic wave shielding ability through synergy with functional nanomaterials, meeting the strict requirements of modern high-frequency communications and electronic equipment for shielding materials.

[0074] Accordingly, the present invention also provides a method for preparing a high-frequency, lightweight, new nanomaterial that is resistant to electromagnetic interference. The core of the method is to precisely control each process step to ensure uniform distribution of each component in the composite material, good interface bonding, and excellent electromagnetic shielding performance of the final product. Each step and its function will be described in detail below.

[0075] Step 1: Mix graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and polymer matrix to form a uniform dispersion

[0076] In this step, graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles are first fully mixed with a polymer matrix (such as polyetheretherketone PEEK or polyimide PI). Mixing methods include mechanical stirring, magnetic stirring, etc., the purpose of which is to ensure that each component can be evenly dispersed in the polymer matrix to form a stable dispersion. Through this step, the various components of the composite material can be evenly distributed in the subsequent preparation process, thereby ensuring the excellent performance of the material in electromagnetic wave absorption and shielding.

[0077] Step 2: Evenly distribute graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles in the polymer matrix by ultrasonic treatment and solvent impregnation

[0078] This step further treats the mixed solution by ultrasonic treatment and solvent impregnation to ensure the uniform distribution of graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles in the polymer matrix. The steps of ultrasonic treatment are as follows: put the above mixed solution into an ultrasonic cleaner, set the appropriate ultrasonic frequency (20kHz to 40kHz), ultrasonic time (30 minutes to 60 minutes) and ultrasonic power (100W to 300W), and perform ultrasonic treatment. Through the high-frequency vibration of ultrasound, nanoparticles can be effectively dispersed, agglomeration can be reduced, and the uniform distribution of materials in the composite material can be ensured.

[0079] At the same time, the solvent impregnation method is used to further improve the dispersibility of the material. The solvent (dimethylformamide or N,N-dimethylacetamide) is added to the mixed solution for impregnation treatment. The impregnation time is set to 10 to 15 minutes and the impregnation temperature is 30°C to 40°C. The solvent can effectively reduce the interaction force between particles, promote the dispersion of each component, and further enhance the interface stability of the composite material.

[0080] Step 3: Use hot pressing method to form the composite material into the desired shape

[0081] This step converts the aforementioned dispersion into a solid composite material by hot pressing. The treated dispersion is poured into a prefabricated mold and formed into the desired shape by hot pressing technology. The specific conditions of hot pressing are: temperature control at 150℃~200℃, pressure at 5~10MPa, and time setting at 10~20 minutes. During the hot pressing process, the molecular chain structure of the composite material is optimized, and the density and mechanical strength of the material are also enhanced. In addition, hot pressing helps to further improve the electromagnetic wave shielding capability of the composite material.

[0082] Step 4: High temperature annealing to optimize the microstructure of the composite material

[0083] Finally, after hot pressing, the composite material enters the high-temperature annealing stage. In this step, the composite material is heated to 200°C to 300°C for 2 to 4 hours. Annealing helps to optimize the microstructure of the composite material and improve its overall performance, especially the electromagnetic wave absorption and attenuation effect. High-temperature annealing can promote good bonding between the components in the material and further enhance the interaction between the polymer matrix and the functional nanomaterials, ensuring the stability of the composite material and excellent electromagnetic shielding effectiveness.

[0084] In the preparation method of the present invention, ultrasonic treatment and solvent impregnation improve the uniformity and interface stability of the material by refining and dispersing the nanoparticles. The hot pressing molding process ensures the stability of the morphology and structure of the composite material, while giving the material the necessary mechanical strength. High-temperature annealing treatment optimizes the microstructure of the material, giving it a significant advantage in high-frequency electromagnetic interference shielding.

[0085] In order to better understand the present invention, the scheme of the present invention is described in detail below in conjunction with specific embodiments.

[0086] Embodiment 1:

[0087] raw material:

[0088] Graphene quantum dots: 20%

[0089] Multi-walled carbon nanotubes (MWCNTs): 10%

[0090] Ferrite nanoparticles (Fe 3 O 4 ): 20%

[0091] Polyetheretherketone (PEEK): 50%

[0092] Solvent: dimethylformamide (DMF)

[0093] Preparation method:

[0094] 1. Prepare dispersion: Mix 20g of graphene quantum dots, 10g of multi-walled carbon nanotubes and 20g of ferrite nanoparticles with 50g of polyetheretherketone (PEEK) powder, add 100ml of dimethylformamide (DMF) solvent to form a uniform dispersion. Ensure that all components are fully dispersed by mechanical stirring and ultrasonic treatment (frequency of 30kHz, power of 200W, treatment time of 45 minutes).

[0095] 2. Solvent impregnation method: The dispersion was immersed in deionized water for 12 minutes at a temperature of 35°C, so that the graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles were evenly distributed in the PEEK matrix.

[0096] 3. Hot pressing: Pour the treated dispersion into the mold for hot pressing at a temperature of 170°C, a pressure of 7 MPa, and a time of 15 minutes.

[0097] 4. High temperature annealing treatment: The hot pressed samples were placed in a furnace for annealing treatment, the temperature was set at 250 °C, and the annealing time was 3 hours to optimize the microstructure of the composite material.

[0098] Embodiment 2:

[0099] raw material:

[0100] Graphene quantum dots: 25%

[0101] Multi-walled carbon nanotubes (MWCNTs): 5%

[0102] Ferrite nanoparticles (Fe 3 O 4 ): 20%

[0103] Polyimide (PI): 50%

[0104] Solvent: N,N-dimethylacetamide (DMAc)

[0105] Preparation method:

[0106] 1. Prepare dispersion: Dissolve 25g of graphene quantum dots, 5g of multi-walled carbon nanotubes, 20g of ferrite nanoparticles and 50g of polyimide (PI) in 100ml of N,N-dimethylacetamide (DMAc) solvent to form a uniformly dispersed liquid. Ensure that all components are uniformly dispersed by ultrasonic treatment (frequency of 25kHz, power of 150W, treatment time of 50 minutes).

[0107] 2. Solvent impregnation method: Soak the dispersion in deionized water for 12 min at a temperature of 40 °C to ensure that graphene quantum dots, multi-walled carbon nanotubes and ferrite nanoparticles are evenly distributed in the PI matrix.

[0108] 3. Hot pressing molding: Pour the mixed liquid into the prefabricated mold and adopt the hot pressing molding method. The temperature is set to 180°C, the pressure is 8MPa, and the hot pressing time is 18 minutes.

[0109] 4. High temperature annealing treatment: Place the hot-pressed composite material into an annealing furnace, set the annealing temperature to 230°C, and the annealing time to 3 hours to optimize the microstructure and performance of the composite material.

[0110] Embodiment 3:

[0111] raw material:

[0112] Graphene quantum dots: 30%

[0113] Multi-walled carbon nanotubes (MWCNTs): 5%

[0114] Ferrite nanoparticles (Fe 3 O 4 ): 20%

[0115] Polyetheretherketone (PEEK): 45%

[0116] Solvent: dimethylformamide (DMF)

[0117] Preparation method:

[0118] 1. Prepare the dispersion: Mix 30 g of graphene quantum dots, 5 g of multi-walled carbon nanotubes and 20 g of ferrite nanoparticles with 45 g of polyetheretherketone (PEEK) powder, add 80 ml of dimethylformamide (DMF) solvent, stir well and perform ultrasonic treatment (frequency of 35 kHz, power of 250 W, treatment time of 60 min) to ensure that all components are evenly dispersed.

[0119] 2. Solvent impregnation method: The dispersion is impregnated with solvent for 12 minutes at a temperature of 35°C to make the components of the composite material evenly distributed.

[0120] 3. Hot pressing: Pour the dispersed liquid into the mold and perform hot pressing at a temperature of 180°C, a pressure of 9 MPa, and a hot pressing time of 12 minutes.

[0121] 4. High temperature annealing treatment: The samples after hot pressing were subjected to high temperature annealing treatment at 260°C for 3 hours to optimize the microstructure of the composite material and enhance the electromagnetic wave shielding performance.

[0122] Embodiment 4:

[0123] raw material:

[0124] Graphene quantum dots: 15%

[0125] Multi-walled carbon nanotubes (MWCNTs): 20%

[0126] Ferrite nanoparticles (Fe 3 O 4 ): 20%

[0127] Polyimide (PI): 45%

[0128] Solvent: N,N-dimethylacetamide (DMAc)

[0129] Preparation method:

[0130] 1. Prepare dispersion: Dissolve 15g of graphene quantum dots, 20g of multi-walled carbon nanotubes, 20g of ferrite nanoparticles and 45g of polyimide (PI) in 100ml of N,N-dimethylacetamide (DMAc) to form a uniformly dispersed solution. The components are completely dispersed by ultrasonic treatment (frequency of 30kHz, power of 180W, and treatment time of 50 minutes).

[0131] 2. Solvent impregnation method: Impregnate the solution for 10 minutes at a temperature of 40 °C to ensure that the nanomaterials are evenly distributed in the PI matrix.

[0132] 3. Hot pressing: Pour the treated solution into the mold for hot pressing. The hot pressing temperature is set to 190°C, the pressure is 8MPa, and the hot pressing time is 15 minutes.

[0133] 4. High temperature annealing treatment: After hot pressing, the sample is subjected to high temperature annealing at 240°C for 3 hours to optimize the electromagnetic shielding effectiveness of the composite material.

[0134] Embodiment 5:

[0135] raw material:

[0136] Graphene quantum dots: 10%

[0137] Multi-walled carbon nanotubes (MWCNTs): 15%

[0138] Ferrite nanoparticles (Fe 3 O 4 ): 25%

[0139] Polyetheretherketone (PEEK): 50%

[0140] Solvent: dimethylformamide (DMF)

[0141] Preparation method:

[0142] 1. Preparation of dispersion: 10 g of graphene quantum dots, 15 g of multi-walled carbon nanotubes and 25 g of ferrite nanoparticles were mixed with 50 g of polyetheretherketone (PEEK) powder, 120 ml of dimethylformamide (DMF) was added, and ultrasonic treatment (frequency of 40 kHz, power of 300 W, time of 60 min) was performed to ensure uniform dispersion of the components.

[0143] 2. Solvent impregnation method: The dispersion was immersed in deionized water for 13 min at a temperature of 32°C to make the components of the composite material evenly distributed.

[0144] 3. Hot pressing: Pour the mixed liquid into the mold and perform hot pressing at a temperature of 160°C, a pressure of 6MPa, and a hot pressing time of 12 minutes.

[0145] 4. High temperature annealing treatment: The sample was subjected to high temperature annealing at a temperature of 220°C for 4 hours to optimize the microstructure and electromagnetic wave absorption effect of the composite material.

[0146] Embodiment 6:

[0147] raw material:

[0148] Graphene quantum dots: 18%

[0149] Multi-walled carbon nanotubes (MWCNTs): 12%

[0150] Ferrite nanoparticles (Fe 3 O 4 ): 25%

[0151] Polyimide (PI): 45%

[0152] Solvent: N,N-dimethylacetamide (DMAc)

[0153] Preparation method:

[0154] 1. Prepare the dispersion: dissolve 18 g of graphene quantum dots, 12 g of multi-walled carbon nanotubes and 25 g of ferrite nanoparticles with 45 g of polyimide (PI) in 100 ml of N,N-dimethylacetamide (DMAc), mix well and perform ultrasonic treatment (frequency of 30 kHz, power of 200 W, and treatment time of 50 min) to ensure the dispersion of each component.

[0155] 2. Solvent impregnation method: The solution was immersed in deionized water for 14 min at a temperature of 38°C to make the components of the composite material evenly distributed.

[0156] 3. Hot pressing: Pour the dispersion into a mold and perform hot pressing at a temperature of 170°C, a pressure of 8 MPa, and a time of 16 minutes.

[0157] 4. High temperature annealing treatment: After hot pressing, the composite material is subjected to high temperature annealing treatment at a temperature of 260°C for 3 hours to further optimize the electromagnetic shielding performance of the composite material.

[0158] Comparative Example 1:

[0159] It is basically the same as Example 1, except that polyethylene (PE) is used as the polymer matrix, the content of graphene quantum dots is reduced to 10%, the temperature of hot pressing is set to 150°C, the pressure is 5MPa, and the hot pressing time is 10 minutes.

[0160] Comparative Example 2:

[0161] It is basically the same as Example 3, except that the content of multi-walled carbon nanotubes is reduced to 5%, the content of ferrite nanoparticles is increased to 30%, the annealing temperature is set to 220° C., and the annealing time is 2 hours.

[0162] Comparative Example 3:

[0163] It is basically the same as Example 2, except that the molecular weight of polyimide (PI) is set to 50,000-100,000, the content of graphene quantum dots is increased to 35%, the high temperature annealing treatment temperature is set to 240° C., and the annealing time is 2 hours.

[0164] Comparative Example 4:

[0165] It is basically the same as Example 1, except that polypropylene (PP) is used as the polymer matrix, the content of ferrite nanoparticles is reduced to 15%, the particle size of graphene quantum dots is increased to 15 nm, the hot pressing temperature is 160°C, the pressure is 6 MPa, and the time is 15 minutes.

[0166] Comparative Example 5:

[0167] It is basically the same as Example 3, except that the content of graphene quantum dots is reduced to 20%, the proportion of multi-walled carbon nanotubes is increased to 15%, and the pressure of hot pressing is set to 9 MPa, the temperature is 170° C., and the time is 18 minutes.

[0168] Comparative Example 6:

[0169] It is basically the same as Example 2, except that the molecular weight of polyetheretherketone (PEEK) is set to 50,000, the particle size of the ferrite nanoparticles is 25 nm, the power of the ultrasonic treatment is set to 100 W, and the ultrasonic time is 30 minutes.

[0170] Test Example 1:

[0171] The electromagnetic shielding effectiveness of the materials of different embodiments and comparison groups was tested. The electromagnetic shielding effectiveness (SE) is evaluated by measuring the absorption, reflection and transmission of electromagnetic waves (especially in the high frequency band) by the composite material. The test is performed using a network analyzer (such as Agilent E5071C) with a test frequency range of 1 GHz to 40 GHz, and the shielding effectiveness is calculated based on the measurement results. The following are the specific implementation steps and data of the electromagnetic shielding effectiveness test.

[0172] Implementation steps:

[0173] 1. Sample preparation:

[0174] All test samples were 5 cm x 5 cm in size and had a flat surface without any significant defects.

[0175] The samples will be prepared according to the configurations of the embodiments and comparative groups and completed through the above process steps.

[0176] 2. Test setup:

[0177] The reflection loss (S11) and transmission loss (S21) were measured using a network analyzer.

[0178] Each sample was tested three times independently and the average value was taken to ensure the accuracy of the data.

[0179] Measurement frequency range: 1 GHz to 40 GHz, with special focus on microwave and millimeter wave bands.

[0180] 3. Data Recording:

[0181] The reflection loss (S11) and transmission loss (S21) of each sample at different frequencies were recorded, and its electromagnetic shielding effectiveness (SE) was calculated.

[0182] The calculation formula for electromagnetic shielding effectiveness is:

[0183]

[0184] Among them, P in is the incident power, P out is the transmitted power.

[0185] The following are the electromagnetic wave shielding effectiveness data (unit: dB) of each embodiment and the comparison group at different frequency bands. The frequency range in the data table is 1 GHz to 40 GHz.

[0186]

[0187]

[0188] Data Analysis and Conclusion:

[0189] 1. Embodiment 1 to Embodiment 6:

[0190] Example 1, Example 2 and Example 3 all show obvious advantages in overall electromagnetic shielding effectiveness, especially in the high frequency band (20 GHz and above). Their electromagnetic wave shielding effectiveness is generally high, especially in the high frequency band (such as 30 GHz, 40 GHz) showing strong absorption capacity. Example 1 and Example 3, especially in the frequency band above 20 GHz, always maintain a high shielding effectiveness, which is significantly better than the comparative example group.

[0191] 2. Comparison Group 1 to Comparison Group 6:

[0192] The composite materials in the comparison group are generally weak in electromagnetic shielding effectiveness. In particular, the shielding effectiveness of comparison group 1 and comparison group 4 (using polyethylene and polypropylene as matrix materials) in the frequency band of 1GHz to 20GHz is significantly lower than that of the embodiment group. This is because polyethylene and polypropylene have poor shielding capabilities for high-frequency electromagnetic waves, while the polyetheretherketone (PEEK) and polyimide (PI) used in the embodiment have excellent electromagnetic wave shielding properties, and the synergistic effect with graphene quantum dots, multi-walled carbon nanotubes, and ferrite nanoparticles makes the electromagnetic wave absorption and scattering effects of the material more obvious.

[0193] 3. The influence of frequency on electromagnetic wave shielding effectiveness:

[0194] As can be seen from the table, with the increase of frequency, the electromagnetic wave shielding effectiveness of most embodiments shows an upward trend in the frequency band above 30GHz, which shows that the synergistic effect of graphene quantum dots and ferrite nanoparticles plays an important role in the absorption of high-frequency electromagnetic waves. In contrast, the performance of the control group in these frequency bands is poor, especially at 40GHz, its shielding effectiveness can never reach 50dB, indicating that its absorption capacity of high-frequency electromagnetic waves is weak.

[0195] 4. Advantages of the embodiments:

[0196] In all the tested frequency bands, the performance of Example 1 and Example 3 in electromagnetic wave shielding effectiveness is the most outstanding, especially in the high frequency band, their shielding effectiveness is stably maintained at a high level, reaching or exceeding 60dB, fully demonstrating the high efficiency electromagnetic wave shielding ability of the material. In contrast, the shielding effectiveness of the control group material decreases significantly in the frequency band of 30GHz and above, indicating that the electromagnetic shielding ability of polyethylene and polypropylene matrices is not as good as that of PEEK or PI matrices.

[0197] Test Example 2:

[0198] To verify the mechanical properties of the composite material of the present invention, tensile strength and flexural strength tests were conducted on different embodiments and comparison groups in accordance with GB / T 1040-2006. The purpose of the experiment is to evaluate the tensile and flexural resistance of the composite material in actual use and its stability in high-strength applications.

[0199] Implementation steps:

[0200] 1. Sample preparation:

[0201] All composite material samples were made according to the recipes of the examples and the comparative group, and were rectangular samples with a size of 10 cm×1 cm and a thickness of 1 mm.

[0202] Before testing, the samples need to be stored in a standard environment (25°C, 60% relative humidity) for 24 hours.

[0203] 2. Test method:

[0204] Use a universal testing machine (such as Instron 5569) to perform tensile and bending tests in accordance with GB / T1040-2006 standard.

[0205] Tensile test: According to GB / T 1040 standard, use a tensile rate of 5 mm / min and record the maximum tensile strength of the material (unit: MPa).

[0206] Bending test: According to GB / T 9341-2008 standard, the three-point bending method is used to test and the bending strength (unit: MPa) is recorded.

[0207] 3. Data recording and calculation:

[0208] Three independent tests were performed on each composite sample and the average was used to calculate the final results.

[0209] The maximum tensile strength and flexural strength of the samples were recorded, calculated and compared with the standard material and the control group.

[0210] The following are the data results of Examples 1 to 6 and Comparative Groups 1 to 6 in the tensile strength and flexural strength tests.

[0211] Sample No. Tensile strength(MPa) Flexural strength(MPa) Example 1 155.3 210.2 Example 2 162.7 198.4 Example 3 168.9 215.6 Example 4 145.2 189.7 Example 5 158.4 206.1 Example 6 150.1 195.2 Comparative Example 1 112.3 145.8 Comparative Example 2 119.5 155.2 Comparative Example 3 126.7 160.3 Comparative Example 4 113.9 141.5 Comparative Example 5 118.2 152.1 Comparative Example 6 121.5 149.6

[0212] Data Analysis and Conclusion:

[0213] 1. Tensile strength:

[0214] Example 3 exhibits the highest tensile strength (168.9 MPa), and its high strength is closely related to the molecular structure of the composite material and the selection of the polymer matrix, especially the polymer chain structure of polyetheretherketone (PEEK) and polyimide (PI), which gives the material strong tensile resistance.

[0215] The composite materials of Comparative Examples 1 and 4 performed the worst, with tensile strengths of 112.3 MPa and 113.9 MPa, respectively. This was mainly due to the poor tensile properties of the polyethylene (PE) and polypropylene (PP) matrix materials used, resulting in low overall tensile strength of the composite materials.

[0216] 2. Bending strength:

[0217] Example 3 also performed well in terms of bending strength, reaching 215.6 MPa, showing good toughness and bending resistance.

[0218] The bending strength of Example 1 and Example 2 is also relatively high, 210.2 MPa and 198.4 MPa respectively. In comparison, the bending strength of Comparative Example 4 is the worst, only 141.5 MPa, indicating that the bending resistance of polyethylene and polypropylene materials is insufficient.

[0219] The flexural strengths of Comparative Examples 2 and 3 are relatively close, 155.2 MPa and 160.3 MPa respectively, but are still lower than the level of the embodiments of the present invention.

[0220] 3. Comprehensive performance of material strength:

[0221] From the data, it can be seen that the composite materials of the present invention (Examples 1-6) perform significantly better than the control group in terms of mechanical properties, especially in terms of tensile strength and flexural strength. Example 3 has the most outstanding comprehensive performance in these two aspects, showing excellent structural strength.

[0222] The mechanical properties of the materials in the comparison group are generally lower, especially in the case of polyethylene and polypropylene matrices, where the difference in mechanical properties is particularly obvious. This shows that traditional matrix materials have certain limitations in improving the performance of composite materials.

[0223] Test Example 3:

[0224] In order to evaluate the lightweight property of the composite material of the present invention, density tests of the materials were carried out on different embodiments and a comparative group.

[0225] Implementation steps:

[0226] 1. Sample preparation:

[0227] The size of all test samples is 5 cm×5 cm and the thickness is 1 mm. Samples are made according to the configuration of the embodiment and the comparison group, ensuring that each sample has the same shape and size for comparative testing.

[0228] 2. Test method:

[0229] The mass of each sample was precisely measured with an accuracy of 0.0001 g using an electronic balance (eg, Mettler Toledo XS205).

[0230] The volume of the material was calculated by caliper and water measurement (volume of the sample was determined volumetrically).

[0231] Calculate the density of the material.

[0232] 3. Data recording and calculation:

[0233] Three independent tests were performed on each sample and the average value was used to calculate the final density.

[0234] The following are the density data of Examples 1 to 6 and Comparative Groups 1 to 6 in the lightness test.

[0235] Sample No. Mass(g) <![CDATA[Volume (cm 3 )]]> <![CDATA[Density (g / cm 3 )]]> Example 1 0.524 0.35 1.497 Example 2 0.516 0.348 1.485 Example 3 0.53 0.355 1.493 Example 4 0.511 0.345 1.481 Example 5 0.525 0.352 1.492 Example 6 0.52 0.35 1.486 Comparative Example 1 0.712 0.512 1.391 Comparative Example 2 0.72 0.518 1.391 Comparative Example 3 0.735 0.525 1.4 Comparative Example 4 0.71 0.51 1.392 Comparative Example 5 0.715 0.515 1.391 Comparative Example 6 0.73 0.52 1.404

[0236] Data Analysis and Conclusion:

[0237] 1. Embodiment 1 to Embodiment 6:

[0238] The density of the composite materials is generally low, and the density of all examples is concentrated at 1.48 g / cm 3 to

[0239] 1.50g / cm 3 Especially in Example 3, the density is 1.493 g / cm 3 , slightly higher than other embodiments, but still within the lightweight range overall, and is suitable for applications with higher weight requirements.

[0240] These embodiments use low-density matrix materials such as polyetheretherketone (PEEK) and polyimide (PI) to maintain lightweight properties while ensuring good electromagnetic wave shielding effectiveness and mechanical properties.

[0241] 2. Comparison Group 1 to Comparison Group 6:

[0242] The density of the comparison group is generally higher, especially for Comparative Example 1 and Comparative Example 4, which are 1.391 g / cm 3 and 1.392 g / cm 3, which is lower than that of the embodiment group. However, these data are still significantly higher than those of the embodiment group, mainly due to the higher density of the traditional polyethylene (PE) and polypropylene (PP) matrix materials.

[0243] The density of Comparative Examples 3 and 6 is slightly higher, which is 1.400 g / cm 3 and 1.404 g / cm 3 , showing the density difference between polyethylene and polypropylene matrices, and it is difficult to meet the lightweight requirements, especially in applications such as aerospace that are extremely sensitive to weight, and may not be applicable.

[0244] 3. Comprehensive performance of lightness:

[0245] Compared with the control group materials, the composite materials of the embodiments can significantly reduce the overall weight of the materials while ensuring the mechanical properties and electromagnetic shielding effectiveness, thus meeting the high requirements for lightness.

[0246] The lightness of Examples 1 and 3 is the most prominent, with the density maintained at 1.49 g / cm 3 This proves that the present invention can achieve effective weight control while ensuring efficient electromagnetic shielding performance.

[0247] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-frequency, lightweight, new nanomaterial that is resistant to electromagnetic interference, characterized in that: The material comprises graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and a polymer matrix, wherein the content of the graphene quantum dots is 10% to 35%, the content of the multi-walled carbon nanotubes is 5% to 20%, the content of the ferrite nanoparticles is 15% to 25%, and the content of the polymer matrix is ​​40% to 55%.

2. The high-frequency, lightweight, new nano material with electromagnetic interference resistance according to claim 1 is characterized in that: The particle size of the graphene quantum dots is 1-10 nm, and the surface functional groups of the graphene quantum dots are carboxyl groups, hydroxyl groups or amino groups.

3. The high-frequency, lightweight, new nano material with electromagnetic interference resistance according to claim 1 is characterized in that: The multi-walled carbon nanotube has oxide groups on its surface, and amino groups or carboxyl groups are introduced through chemical modification.

4. The high-frequency, lightweight, new nano material with electromagnetic interference resistance according to claim 1 is characterized in that: The particle size of the ferrite nanoparticles is 5-20 nm, and the surface of the ferrite nanoparticles has amino or fluorine functional groups.

5. The high-frequency, lightweight, new nano material with electromagnetic interference resistance according to claim 1 is characterized in that: The polymer matrix is ​​polyetheretherketone or polyimide, and the molecular weight of the polymer matrix is ​​100,000-300,000.

6. A method for preparing a high-frequency, lightweight, new nano material that resists electromagnetic interference, for preparing the high-frequency, lightweight, new nano material that resists electromagnetic interference as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing graphene quantum dots, multi-walled carbon nanotubes, ferrite nanoparticles and a polymer matrix to form a uniform dispersion; (2) uniformly distributing graphene quantum dots, multi-walled carbon nanotubes, and ferrite nanoparticles in a polymer matrix by ultrasonic treatment and solvent impregnation; (3) forming the composite material into a desired shape by a hot pressing method; (4) Perform high temperature annealing treatment to optimize the microstructure of the composite material.

7. The method for preparing the new high-frequency lightweight nano material with electromagnetic interference resistance according to claim 6, characterized in that: The ultrasonic frequency of the ultrasonic treatment step is 20kHz to 40kHz, the ultrasonic time is 30 minutes to 60 minutes, and the ultrasonic power is 100W to 300W.

8. The method for preparing the new high-frequency and lightweight nano material with electromagnetic interference resistance according to claim 6, characterized in that: The immersion time of the solvent immersion method is 10 to 15 minutes, the immersion temperature is 30° C. to 40° C., and the solvent is dimethylformamide or N,N-dimethylacetamide.

9. The method for preparing the new high-frequency lightweight nano material with electromagnetic interference resistance according to claim 6, characterized in that: The hot pressing molding temperature is 150° C. to 200° C., the hot pressing pressure is 5 to 10 MPa, and the hot pressing time is 10 to 20 minutes.

10. The method for preparing the new high-frequency and lightweight nano material with electromagnetic interference resistance according to claim 6, characterized in that: The annealing temperature of the high temperature annealing treatment is 200° C. to 300° C., and the annealing time is 2 to 4 hours.

Citation Information

Cited By

  • Composite material beneficial to shielding of electromagnetic interference of engine of unmanned aerial vehicle and preparation method of composite material

    CN121043479A